(3efXheI CeGdis - (3Ydj Hf YKeGf Hf SdjeGf Hf eMeO GdJjej GdGhSj (B((3GdGhTj(B) (3GdaQZGfj GdMfaj, CHh GdMSf SQGL GdOjf CHh eMeO GdGhTj,J (B569 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO ai HOA GdCeGdi s
(3Vef eLehY , JQJjHgG (B: (3GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B475s
Keywords: (3GdbQGAGJ hGdJLhjOs